The prestigious maize inbred lines and hybrids with erect top leaves are characterised by a property of an efficient photosynthetic model and a satisfactory base for the further progress in breeding and selection - Radenović, Č.N.; Grodzinskij, D.M.; Filipović, M.R.; Radosavljević, M.M.; Videnović, Ž.V.; Denić, M.P.; Čamdžija, Z.F. (Физиология и биохимия культурных растений, 2010)
This study conforms the hypothesis that elite maize inbred lines with erect top leaves and hybrids, in which they are included as parents, have a dominant property of an efficient photosynthetic-fluorescence model and that as such are successfully used in breeding and modern production technology of hybrid seed and commercial maize.